Trastuzumab-mediated cardiotoxicity: current understanding, challenges, and frontiers - Mohan, Nishant (Antib Ther, 2018)
Trastuzumab, an epidermal growth factor receptor 2 (HER2) targeting humanized monoclonal antibody, has been approved for the treatment HER2-positive breast cancer and HER2-positve metastatic gastric cancer. However, cardiotoxicity associated with its clinical application poses challenges for clinicians and patients, mechanisms of which are still evolving. This review will summarize the current mechanistic understanding of trastuzumab-mediated cardiotoxicity, discuss the novel role of DNA topoisomerase IIB as a shared target for enhanced cardiotoxicity induced by trastuzumab and anthracyclines-based combination regimens, and speculate the potential impact of trastuzumab intervention in immune checkpoint inhibitors-based therapies.